Cognitive enhancement and antipsychotic-like activity following repeated dosing with the selective M4 PAM VU0467154. (January 2018) - Gould, Robert W.; Grannan, Michael D.; Gunter, Barak W.; Ball, Jacob; Bubser, Michael; Bridges, Thomas M.; Wess, Jurgen; Wood, Michael W.; Brandon, Nicholas J.; Duggan, Mark E.; Niswender, Colleen M.; Lindsley, Craig W.; et al.
Abstract: Although selective activation of the M1 muscarinic acetylcholine receptor (mAChR) subtype has been shown to improve cognitive function in animal models of neuropsychiatric disorders, recent evidence suggests that enhancing M4 mAChR function can also improve memory performance. Positive allosteric modulators (PAMs) targeting the M4 mAChR subtype have shown therapeutic potential for the treatment of multiple symptoms observed in schizophrenia, including positive and cognitive symptoms when assessed in acute preclinical dosing paradigms. Since the cholinergic system has been implicated in multiple stages of learning and memory, we evaluated the effects of repeated dosing with the highly selective M4 PAM VU0467154 on either acquisition and/or consolidation of learning and memory when dosed alone or after pharmacologic challenge with the N-methyl-d -aspartate subtype of glutamate receptors (NMDAR) antagonist MK-801. MK-801 challenge represents a well-documented preclinical model of NMDAR hypofunction that is thought to underlie some of the positive and cognitive symptoms observed in schizophrenia. In wildtype mice, 10-day, once-daily dosing of VU0467154 either prior to, or immediately after daily testing enhanced the rate of learning in a touchscreen visual pairwise discrimination task; these effects were absent in M4 mAChR knockout mice. Following a similar 10-day, once-daily dosing regimen of VU0467154, we also observed 1) improved acquisition of memory in a cue-mediated conditioned freezing paradigm, 2) attenuation of MK-801-induced disruptions in the acquisition of memory in a context-mediated conditioned freezing paradigm and 3) reversal of MK-801-induced hyperlocomotion. Comparable efficacy and plasma and brain concentrations of VU0467154 were observed after repeated dosing as those previously reported with an acute, single dose administration of this M4 PAM. Together, these studies are the first to demonstrate that cognitive enhancing and antipsychotic-like activity are not subject to the development of tolerance following repeated dosing with a selective M4 PAM in mice and further suggest that activation of M4 mAChRs may modulate both acquisition and consolidation of memory functions. Highlights: Antipsychotic drugs (APDs) do not improve cognitive impairments in Schizophrenia. M4 muscarinic acetylcholine receptors (mAChR) represent a novel target for developing APDs. VU0467154 is a potent M4 mAChR positive allosteric modulator with APD-like effects. 10-day repeated dosing of VU0467154 improves memory acquisition and consolidation in mice. 10-day repeated dosing blocks MK-801-induced hyperlocomotion in mice.